Optimizing Reading Ability Through the CIRC Model Assisted by Story Card Media in the Context of Multicultural Education in Elementary Schools - Aiman, Ummu; Sudiana, I Nyoman; Bagus Putrayasa, Ida (Kawanua International Journal of Multicultural Studies, 2023)
This research aims to analyze how the CIRC model assisted by story card media can support multicultural education in elementary schools. The research used is classroom action research (CAR), with research procedures including planning, action, observation and reflection. The subjects used were 24 first grade students consisting of 14 boys and 10 girls. The achievement results at the initial observation showed that, of the 24 students, only 6 (27%) students were in the capable reading category. In the first cycle, as many as 6 (33.3%) students were able to read, 18 students (66.7%) were in the unable to read category. The number and percentage increased in the second cycle to 24 (100%) students who were able to read. Based on the results of the research and discussion above, it can be concluded that through the Cooperative Integrated Reading and Composition (CIRC) model it can improve reading skills for first grade students at SD Inpres Tenubot, Belu Regency. The use of story card media in the CIRC model adds an inclusive and interactive dimension to the learning process, allowing students to explore various themes and stories that reflect cultural diversity.